2021
DOI: 10.3390/ijerph18126333
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patterns of Symptom Distress in Pregnant Women: A Pilot Study

Abstract: During pregnancy, a woman’s enlarged uterus and the developing fetus lead to symptom distress; in turn, physical and psychological aspects of symptom distress are often associated with adverse prenatal and birth outcomes. This study aimed to identify the trends in the trajectory of these symptoms. This longitudinal study recruited 95 pregnant women, with a mean age of 32 years, from the prenatal wards of two teaching hospitals in northern Taiwan. Symptom distress was measured by a 22-item scale related to preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Significant differences in physical symptoms were observed across the three trimesters, and higher physical SD scores were recorded at all time points than psychological SD scores, with no significant differences in psychological symptoms across the trimesters. The SD trajectories observed in our study were consistent with those reported previously (Lee et al, 2021). In addition, we found that total PA among pregnant women in our study cohort exhibited a downward trend, but the opposite trend was observed for SD.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Significant differences in physical symptoms were observed across the three trimesters, and higher physical SD scores were recorded at all time points than psychological SD scores, with no significant differences in psychological symptoms across the trimesters. The SD trajectories observed in our study were consistent with those reported previously (Lee et al, 2021). In addition, we found that total PA among pregnant women in our study cohort exhibited a downward trend, but the opposite trend was observed for SD.…”
Section: Discussionsupporting
confidence: 93%
“…Our study has several strengths. Our study recruited a larger sample of pregnant women than previous studies (Beebe et al, 2017; Lee et al, 2021) and explored the changes in SD and PA and their correlations during pregnancy, following pregnant women from the first through the third trimester. To our knowledge, most studies of SD and PA among pregnant women assess either PA alone or a single symptom and are typically limited to a single trimester (Caputo et al, 2019; Liu et al, 2020; Sinclair et al, 2019), with no prior studies providing a comprehensive overview of changes over time or the relationships between physical and psychological SD and PA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations